Mental well-being of international migrants to Japan: a systematic review - Akira Shibanuma; Masamine Jimba; Russell Miller; Yuri Tomita; Ken Ing Cherng Ong (BMJ Open)
Background Migration is a stressful process of resettlement and acculturation that can often negatively impact the mental health of migrants. International migration to Japan, a country with dominant ethnic homogeneity, is growing steadily amid an ageing domestic population and severe labour shortages.Objectives To identify the contemporary barriers to, and facilitators of, mental well-being among the migrant population in Japan.Design Systematic reviewData sources PubMed, ProQuest, Web of Science, Ichushi and J-StageEligibility criteria Research articles examining the mental well-being of international migrants in Japan that were published in English or Japanese between January 2000 and September 2018 were included.Data extraction and synthesis Full texts of relevant articles were screened and references of the included studies were hand-searched for further admissible articles. Study characteristics, mental well-being facilitators and barriers, as well as policy recommendations were synthesised into categorical observations and were then thematically analysed.Results Fifty-five studies (23 published in English), surveying a total of 8649 migrants, were identified. The most commonly studied migrant nationalities were Brazilian (36%), followed by Chinese (27%) and Filipino (8%). Thematic analysis of barriers to mental well-being among migrants chiefly identified ‘language difficulties’, ‘being female’ and ‘lack of social support’, whereas the primary facilitators were ‘social networks’ followed by ‘cultural identity’. Policy recommendations for authorities generally described more migrant support services and cross-cultural awareness among the Japanese public.Conclusion Access to social support networks of various types appears to be an influential factor affecting the mental well-being of international migrants in Japan. More research is necessary on how to promote such connections to foster a more inclusive and multicultural Japanese society amid rapid demographic change.PROSPERO registration number CRD42018108421.